Comparison of Microbial Populations in Saliva and Feces from Healthy and Celiac Adolescents with Conventional and Molecular Approaches after Cultivation on Gluten-Containing Media: An Exploratory Study - Tilen Senicar; Andraz Kukovicic; Valerija Tkalec; Aleksander Mahnic; Jernej Dolinsek; Maja Rupnik (Microorganisms, 2021)
Microbes capable of metabolizing gluten are common in various parts of the intestinal tract. In this study, saliva and fecal samples were obtained from 10 adolescents (13–18 years of age), five of which had celiac disease (CD) and five of which were healthy volunteers (HV). Culture-enriched saliva and fecal samples were compared with molecular profiling, and microorganisms displaying lysis zones on gluten-containing media (i.e., gluten-degrading microorganisms; GDMs) were isolated. In total, 45 gluten-degrading strains were isolated, belonging to 13 genera and 15 species, including Candida albicans and Veillonella. GDMs were more common in HVs compared to CD patients and more diverse in saliva compared to feces. In saliva, GDMs showed partial overlap between HVs and CD patients. Bacterial communities in fecal samples determined with amplicon sequencing significantly differed between CD patients and HVs. Overall, 7–46 of all operational taxonomic units (OTUs) per sample were below the detection limit in the fecal samples but were present in the cultivated samples, and mainly included representatives from Lactobacillus and Enterococcus. Furthermore, differences in fecal short-chain fatty-acid concentrations between CD patients and HVs, as well as their correlations with bacterial taxa, were demonstrated.